ONDCP issues first 'treatment plan': Not part of Strategy. Issue 6 (7th February 2020) - Knopf, Alison
Abstract : Last week, in a surprise move, the Office of National Drug Control Policy (ONDCP) issued its first National Treatment Plan for Substance Use Disorder, along with its National Drug Control Strategy. If anyone was expecting an additional windfall like the $1 billion annual State Opioid Response grant program, it's not there.